Methane Efflux Measured by Eddy Covariance in Alaskan Upland Tundra Undergoing Permafrost Degradation. Issue 9 (7th September 2018) - Taylor, M. A.; Celis, G.; Ledman, J. D.; Bracho, R.; Schuur, E. A. G.
Abstract: Greenhouse gas emissions from thawing permafrost in arctic ecosystems may amplify global warming, yet estimates of the rate of carbon release, and the proportion of carbon released as methane (CH4 ) or carbon dioxide (CO2 ), have a high degree of uncertainty. There are many areas where no measurements exist, and few year‐round or long‐term records. Existing year‐round eddy covariance measurements of arctic CH4 fluxes suggest that nongrowing season emissions make up a significant proportion of tundra systems emissions on an annual basis. Here we present continuous CH4 flux measurements made at Eight Mile Lake, an upland tundra ecosystem undergoing permafrost degradation in Interior Alaska. We found net CH4 emissions throughout the year (1.2 ∓ 0.011 g C‐CH4 m 2 /yr) that made up 61% of total radiative forcing from annual C emissions (CO2 and CH4 ; 32.3 g C m 2 /yr) when taking into account the greenhouse warming potential of CH4 relative to CO2 . Nongrowing season emissions accounted for 50% of the annual CH4 budget, characterized by large pulse emissions. These were related to abrupt increases in air and shallow soil temperatures rather than consistent emissions during the zero curtain—a period of the fall/early winter season when subsurface soil temperatures remain near the 0 °C freezing point. Weekly growing season CH4 emissions in 2016 and 2017 were significantly related with thaw depth, and the magnitude of CH4 emissions between these seasons was proportional to the rate of active layer thaw throughout the season. Key Points: Arctic permafrost tundra ecosystem is an annual net source of CH4 Nongrowing season emissions make up 45% of annual CH4 loss Thaw depth is a significant driver of growing season CH4 emissions